Looking beyond PPHN: the unmet challenge of chronic progressive pulmonary hypertension in the newborn - Fike, Candice D. (University of Chicago Press, 2013)
Abstract. Infants with forms of pulmonary hypertension (PH) that persist or develop beyond the first week of life are an understudied group of patients with up to 40%–60% mortality. The clinical management of the progressive PH that develops in these infants is challenging because of the nonspecific signs and symptoms of clinical presentation, the limited diagnostic sensitivity of standard echocardiographic techniques, and the lack of proven therapies. The signaling mechanisms that underlie the structural and functional abnormalities in the pulmonary circulation of these infants are not yet clear. The ability to improve outcomes for these patients awaits technological advances to improve diagnostic capabilities and therapeutic discoveries made in basic science laboratories that can be tested in randomized clinical trials.